DNA Methylation of ABC Transporters Differs in Native and Non-native Populations of Conyza canadensis L. - Ambreen Tahir Shah; Ambreen Tahir Shah; Zafar A. Reshi; Mohammad Altaf; Mohammad Altaf (Frontiers in Ecology and Evolution, 2022)
While differences in the methylation patterns of ABC transporters under different environmental conditions and their role in plant growth, development, and response to biotic and abiotic stresses are well documented, less is known about the variation in the methylation patterns of ABC transporters in plant species in the native and non-native ranges. In this study, we present the results of differences in methylation of ABC transporters of Conyza canadensis L. in its native (North America) and non-native (Kashmir Himalaya) ranges. Our data show that ABC transporter genes have reduced DNA methylation in Kashmir Himalaya than in North America. Furthermore, in the non-native range of Kashmir Himalaya, we found that ABC transporter genes have enriched RNA Pol-II binding and reduced nucleosome occupancy, both hallmarks of transcriptional activity. Taken together, our study showed differential DNA methylation in the ABC transporter genes in the native range of North America and non-native range of Kashmir Himalaya in Conyza canadensis and that the reduced DNA methylation and increased RNA Pol-II binding is one of the possible mechanisms through which this species in the non-native range of Kashmir Himalaya may show greater gene expression of ABC transporter genes. This increased ABC transporter gene expression may help the plant to grow in different environmental conditions in the non-native range. Furthermore, this study could pave way for more studies to better explain the enigmatic plant invasions of C. canadensis in the non-native range of Kashmir Himalaya.